Morphological study of variation in shape of coronoid process of mandible in dry human bone in Mahakaushal region - Rajeshwari Kanwar; Ranjana Agrawal (International Journal of Medical Research and Review, 2018)
Introduction: The coronoid process is present at the ramus of mandible bone. The coronoid process projects upwards and slightly forwards as a triangular plate of bone. The variations in shape of coronoid process may acts as anthropological markers, to assess different populations & races. It may also be useful in forensic studies for determination of gender. With keeping above facts in mind, present study was planned.Material methods: The shape of the coronoid processes of both sides of 52 dry adult human mandibles (29 male and 23 female) were studied to classify the variations. The study was conducted in NSCB Medical College, Jabalpur. Three types of shapes were observed which are hooked, triangular and round shaped.Results: Triangular shape of coronoid process was present in 48.08% mandibles. It was of rounded shape in 19.23% mandibles. In 32.69% mandibles found hooked shaped. out of total 52 mandibles, in 29 belonging to male, triangular shape was found in 36.21%, rounded shape in 22.41% and hooked shape was found in 41.37% mandibles. Out of remaining 23 mandibles which were of females, triangular shape was found in 63.04%, rounded shape in15.22% and hooked shape in 21.74% mandibles.Conclusion: In present study, it is found that hooked shape coronoid is more common in male mandibles and in females, most common shape is triangular. As, no study was done previously at shapes of coronoid process at Mahakaushal area, hence, present study may be useful for maxillofacial surgeons and forensic experts especially of Mahakaushal region.